To Find the Effect of Microsurgical Varicocelectomy on Sperm Motility in Infertile Men - Mir Abid Jan, Irshad Khan, Muhammad Shahid Bhatti, Shahjehan, Khadija Saleem, Khalil Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Varicocele is a common cause of male infertility, significantly impacting sperm motility and count. Microsurgical varicocelectomy is a widely accepted treatment for varicocele, aimed at improving semen parameters and fertility potential in affected men. Objective: This study aimed to evaluate the effect of microsurgical varicocelectomy on sperm motility and sperm count in infertile men with clinical varicocele. Material and Methods: This prospective interventional study was conducted at Institute of Kidney Diseases, MTI - Hayatabad Medical Complex, Peshawar, from October 2022 to March 2023. A total of 23 infertile men with clinically palpable varicocele (Grades I–III) were enrolled. Participants underwent subinguinal microsurgical varicocelectomy performed by an experienced surgeon. Semen analysis, assessing sperm motility and sperm count, was performed pre-operatively and three months post-operatively. Data were analyzed using SPSS version 25, and statistical significance was determined using paired t-tests with a p-value of <0.05. Results: Significant improvements were observed in sperm motility and sperm count post-operatively. Mean sperm motility increased from 24.95% (±2.967) to 41.98% (±4.353) (p<0.001), while mean sperm count improved from 2.97 million/mL (±1.168) to 9.85 million/mL (±2.994) (p<0.001). These improvements were consistent across age groups, varicocele grades, and infertility durations, with non-obese participants showing more pronounced benefits. Conclusion: Microsurgical varicocelectomy significantly improves sperm motility and sperm count in infertile men with varicocele. It is an effective treatment option for enhancing semen parameters and addressing male infertility. Keywords: Varicocele, Microsurgical varicocelectomy, Male infertility, Sperm motility, Sperm count